Mobile application for fresh food ordering - Nurul Amanina, Ramli (2019)
In this century, many advances in mobile technology have been created to help the community in their lives. Mobile Application for Fresh Food Ordering is developed for everyone in Malaysia to place fresh food orders remotely from different locations via mobile devices. Not only that, but it also facilitates sellers of fresh food to provide services send fresh food to customers. Nowadays morning market and supermarket still using the old-fashioned approach, which is customer need to line up in long queues and squeeze to buy fresh food, especially at the peak hour. Because of that, this old-fashioned approach takes a lot of time and wasting customer time. Besides that, because due to the limited availability of offline market and each market has space constraints so it does not have a lot of choices to choose fresh food. Hence, this will waste customer money and does not meet customer requirements. So, the purpose of this project is to provide customers with fresh food requesting service, pointing to dealer's location with this application using GPS and Google Map graphical user interface. As a result, it is easier for customers to buy fresh items without having to go to the morning market and supermarket and save customers time.